2007
DOI: 10.1590/s0034-89102007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade da informação sobre mortalidade por violência em Belo Horizonte, MG

Abstract: OBJECTIVE:To determine reliability of data encoding for death due to violence; to assess the agreement between cause of death in the Mortality Information System and cause selected from the Forensic Medicine Institute database; and to assess the impact of adding information of non-specified injuries and undetermined death events subsequently obtained from Forensic Medicine Institute in the mortality statistics due to violence. METHODS:A random sample of 411 death certificates due to violence was obtained in Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 12 publications
(20 reference statements)
1
21
0
10
Order By: Relevance
“…These authors also found similar numbers in Londrina and Ponta Grossa -PR 3 . This fact was also observed in one Northeast region's capital 6 and in Mexico 21 . The data relating specifically to the deaths of motorcyclists cannot be evaluated in this study due to failure to complete the statements, as will be explained below, but it is becoming a trend nowadays.…”
Section: Results Results Results Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…These authors also found similar numbers in Londrina and Ponta Grossa -PR 3 . This fact was also observed in one Northeast region's capital 6 and in Mexico 21 . The data relating specifically to the deaths of motorcyclists cannot be evaluated in this study due to failure to complete the statements, as will be explained below, but it is becoming a trend nowadays.…”
Section: Results Results Results Resultssupporting
confidence: 61%
“…In fact, other authors found discrepancies between the results of autopsies and reports cadaveric and death certificates officially registered in Brazil. They also concluded that there is a need to improve the coding and selection of underlying cause, improvements in completing death certificates by coroners and in medical and police information in the documents referring bodies for autopsy, especially for RTAs and falls 21,22 . There was also difficulty in obtaining the information, since the Coroner's Office records are not electronic, but printed, without standardization of information.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…The lower proportion of ill-defined deaths in men of productive age compared with women may be related to the higher occurrence of external causes among them. These deaths are certified by coroners after autopsy reports and the circumstances of the injuries are investigated in police reports by the municipal health department, leading to a specific diagnosis of the cause of death 14 . When analyzing the occurrence of the five main GC groups -other ill-defined and unspecified causes of mortality, unspecified pneumonias, stroke unspecified as hemorrhagic or ischemic, unspecified septicemia and other specified cerebrovascular diseases -the importance of a better understanding of the concept of GC is evident given that such causes offer information of little use to support planning for specific health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Esses estudos também mostram que independente das orientações e treinamentos realizados durante décadas para o preenchimento da BO, os legistas permanecem informando apenas a natureza das lesões e falhando no fluxo dos encaminhamentos de corpos para necropsia 8,20,21,22 . Este fato interfere diretamente na qualidade dos dados do SIM, o qual possui tanto instrumento quanto fluxo de informação melhor definidos.…”
Section: Considerações éTicasunclassified